Management of neobladder complications: endoscopy comes first. (4th March 2017) - Moeen, Ahmed M.; Safwat, Ahmed S.; Elderwy, Ahmad A.; Behnsawy, Hosny M.; Osman, Mahmoud M.; Hameed, Diaa A.
Abstract: Objective: The aim of this study was to report the functional outcome after endoscopic management of neobladder complications. Materials and methods: Out of 197 patients who underwent radical cystectomy and orthotopic ileal neobladder reconstruction between 2007 and 2013, 30 patients with delayed postoperative complications were enrolled in this study. Complications were in the form of: eight patients with outflow obstruction, 12 with ureteroenteric stricture, nine with neobladder calculi and one with an isolated recurrent papillary tumor inside the neobladder. Patients were followed up regularly to assess the outcomes of endoscopic treatment. Results: The mean maximum flow rate and postvoiding residual urine after endoscopic treatment of outflow obstruction were 18.2 ± 3.9 ml/s and 28.7 ± 11 ml, respectively. Ten patients with ureteroenteric stricture showed resolution of hydronephrosis after antegrade dilatation and JJ-stent fixation, with two patients requiring open surgery owing to impassable strictures. Complete clearance of neobladder calculi occurred after endoscopic neocystolithotripsy, with two patients requiring two sessions owing to large calculi. Transurethral resection of the neobladder for isolated tumor recurrence was performed in one patient over two sessions, followed by adjuvant chemoirradiation. Conclusions: Endourological management of orthotopic neobladder problems is the safest choice. It avoids the difficulties and complications of open surgery and has durable results.